Preface: 5th International Conference on Computer Engineering, Information Science and Internet Technology (CII 2023) - Symons, Lawrence; Zhu, Xiaoming (Transactions on Computer Science and Intelligent Systems Research, 2023)
The organizing Committee of CII 2023 warmly welcomes you to join the 5th International Conference on Computer Engineering, Information Science and Internet Technology (CII 2023), which was held on November 11-12, 2023 in Sanya, China.On the move towards the 21st century, Computer Engineering, Information Science and Internet Technology are the important tools to solve the global problems, e.g. the energy and environmental problems, as well as to foster the prosperities for a better life. They are created from the simple ideas that make the difference, the ideas that connect the dots of different fields of knowledge.Thus, the objective of this conference is to gather engineers, scientists and innovators to share their new findings and ideas in different fields of knowledge. This is to share their experiences in specific domains as well as across the fields with the aim at provoking emerging innovative ideas and further collaborations.Hopefully, all participants and other interested readers benefit scientifically from the proceedings and also find it stimulating in the process.Lawrence Symons, Xiaoming ZhuConference Organizing Chair